2022
DOI: 10.3389/fenvs.2022.844479
|View full text |Cite
|
Sign up to set email alerts
|

Investigate the Effects of Industrial Agglomeration on Nitrogen Dioxide Pollution Using Spatial Panel Durbin and Panel Threshold Models

Abstract: The degree of industrial agglomeration in China has contributed to the reduction of nitrogen dioxide pollution because of financial support, the allocation of environmental governance efficiency, and technological advantages. However, the intensity and scope of the spatial effect of this contribution needs to be studied in depth. Based on the influence mechanism and intermediate mechanism of the spatial pattern, this paper uses the panel data of 282 prefecture-level and above cities in China from 2015 to 2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Results as shown in Table 3 , the LM and LR tests' statistics are significant at 1% level, which indicates that it is necessary to use the spatial measurement method for analysis. Compared with spatial lag and error models, the spatial Durbin model has more advantages in alleviating estimation errors ( 35 ). The Hausman test shows that this paper must control the time fixed effect and individual fixed effect in the spatial Durbin model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results as shown in Table 3 , the LM and LR tests' statistics are significant at 1% level, which indicates that it is necessary to use the spatial measurement method for analysis. Compared with spatial lag and error models, the spatial Durbin model has more advantages in alleviating estimation errors ( 35 ). The Hausman test shows that this paper must control the time fixed effect and individual fixed effect in the spatial Durbin model.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, environmental pollution can produce cross-border pollution through spatial diffusion ( 34 ). Therefore, many scholars have discussed the spatial spillover effects of key variables when discussing environmental pollution ( 35 , 36 ). Thus, this paper uses a spatial econometric model to discuss the spatial correlation effect of environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, industrial agglomeration can promote technology sharing, matching, and learning by building symbiotic and mutually beneficial relationships between industries. Furthermore, enterprises can effectively reduce industrial pollutant emissions by sharing pollution treatment technologies and equipment ( 22 ). On the other hand, some studies have concluded that although technological progress has improved the production efficiency and expanded production scale, it has not made the production process more environmentally friendly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ge et al, (2022) (Ge et al, 2022) used the spatial Durbin model to study the impact of economic growth targets on CO 2 emissions. Han et al, (2022) (Han et al, 2022) used panel data from 282 prefecture level cities in China, and adopted spatial Durbin and STIRPAT models to study the impact of industrial agglomeration on nitrogen dioxide emissions. Thus, when it comes to air pollution, it is more proper using spatial models, and consider the spatial spillover effect like most scholars do (Jiang et al, 2022) instead of ordinary panel models.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%